Jigsaw versus Conventional Method towards Children’s Attitude and Knowledge of Dental and Oral Health - Alphianti, Likky Tiara; Mei, Ariska (Indonesian Dental Association, 2019)
Introduction: The effort in improving dental and oral health could be taken by giving information about oral and dental health as early as possible. Jigsaw cooperative learning method and conventional learning method are two of several learning methods that commonly used in order to giving information about dental and oral health. Objectives: The purpose of this study was to determine the comparison between both learning methods between, jigsaw cooperative and conventional, towards children’s attitude and knowledge of dental and oral health. Methods: This study was a quasi-experimental with non-randomized control group pre-test and post-test design. Sixty-eight students aged 10-11 from Muhammadiyah Suronatan Yogyakarta Elementary School was taken as the subjects and divided into 2 groups. Group A (n=36) was jigsaw cooperative learning method group and group B (n=32) was conventional learning method group. Each subject fulfilled two types questionnaire before and after giving lecture, such as attitude’s questionnaire and knowledge’s questionnaire of dental and oral health. Data were analyzed using paired t-test and independent t-test. Results: From the result of paired t-test, it showed that there were significant differences between before and after treatment in both groups at knowledge aspect (Group A: p=0.000 and group B: p=0.015) as well as attitude aspect (group A and B; p=0.000 respectively). Independent t-test showed there were significant differences between both groups in knowledge (p=0.003) and attitude (p=0.000). Conclusion: In this study, there were significant difference between jigsaw cooperative learning method and conventional learning method at knowledge and attitude aspects in children aged 10-11 years old. Children in group jigsaw cooperative learning method have higher score than children in group conventional learning method.